Developing ESP E-Module Course Design Based on Canva for Law Students - Rini Dwi Septiyani; Iron Fajrul Aslami; Dewi Surani (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2022)
This research aims to design and develop an e-module based on the Canva application, and to measure the validity of e-modules for legal English courses. This research uses Research and Development (R&D) research with the ADDIE model with five stages: first is analyzing problems, potentials, and needs. The second is designing to determine a Canva Digital application used, the design/theme of the e-module, and the format. The third stage is developing the design that has been previously designed by being developed through the Canva Digital application. In addition, at this stage, a validation test is carried out for the validators, namely material experts, linguists, and media experts to determine the feasibility of the E Module that has been designed and developed. The fourth stage is Implementation. In this stage, a practicality test and effectiveness test are carried out on law students of Bina Bangsa University. The final stage is evaluation, at this evaluation stage, is the stage of implementing digital Canva-based E-Module improvements that have been given input by material experts, linguists, and media experts. Quantitative and qualitative data were employed to collect the information. The finding reveals the average score for eligibility assessment results is 91,79 %, the average score for practicality assessment results is 91,86 %, and the average score for effectiveness is  84,66. In conclusion, the eligibility assessment is classified as "Very Eligible," the practicality  assessment derived from the lecture and student practicality questionnaires is classified as "Very Practical," and the effectiveness assessment derived from the evaluation activities is classified as "Very Effective." E-module teaching materials can be utilized by lecturers as an alternate method of transmitting information on the ESP to law students, allowing lecturers to provide information in a manner that captures students' attention. The e-module was still developed utilizing an online connection, which presented a challenge for students who did not have consistent access to the internet. For the upcoming research, it is strongly suggested that an electronic module be developed that can be accessed either online or off.